How to cope with snow and ice: winter ecology of feral Greylag Geese Anser anser - Käßmann, Sonja; Woog, Friederike (Wildfowl, 2013)
Unlike most wild goose populations in the Western Palaearctic, the feral Greylag Geese Anser anser in Stuttgart, southwest Germany, are not known to migrate. In winter 2004/05, a study was carried out to determine how this resident group copes with snow and ice, since severe weather conditions are not unusual in the region. Changes in activity budgets, feeding behaviour and abdominal fat reserves were investigated. From January to March 2005, frequent snowfall resulted in persistent snow cover. In response to the resulting lack of food, the geese changed their daily feeding patterns, fed less, loafed more and subsequently lost abdominal fat reserves. Although they moved from small park lakes to the ice-free river for roosting, they did not leave the area in search of snow-free feeding sites.